2021
DOI: 10.1039/d1ta02433g
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous titanium niobium nitrides supported Pt nanoparticles for highly selective and sensitive formaldehyde sensing

Abstract: A highly sensitive and selective formaldehyde sensor is prepared by using mesoporous Ti0.75Nb0.25N supported Pt NPs as a high efficiency gas sensing electrode material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 58 publications
(54 reference statements)
0
5
0
Order By: Relevance
“…2i , the BE of Pt loaded on TiN@C is less than that of the Pt/TiN, that is, the electronic structure and SMSI still exists. Previous study have pointed out that there is a strong interaction between Pt NPs and transition metal nitrides, 22 and the smaller Pt NPs we prepared are more conducive to produce and strengthen the SMSI. 23 Based on the change in BE between Pt and N, the interaction between Pt and TiN mainly originates from the interaction between Pt and N. The SMSI makes the diffusion barrier of Pt on the support surface higher.…”
mentioning
confidence: 74%
“…2i , the BE of Pt loaded on TiN@C is less than that of the Pt/TiN, that is, the electronic structure and SMSI still exists. Previous study have pointed out that there is a strong interaction between Pt NPs and transition metal nitrides, 22 and the smaller Pt NPs we prepared are more conducive to produce and strengthen the SMSI. 23 Based on the change in BE between Pt and N, the interaction between Pt and TiN mainly originates from the interaction between Pt and N. The SMSI makes the diffusion barrier of Pt on the support surface higher.…”
mentioning
confidence: 74%
“…While the τ rec was long, primarily because the energy obtained from RT was much lower than the activation energy for linalool molecule desorption [34]. In view of practical application of the as-developed sensor, an outstanding capability is to distinguish linalool from various atmospheres [35]. We also investigated the selectivity of all the sensors towards 20 ppm of different kinds of target gases (NH 3 , NO 2 , CO 2 , C 9 H 18 O, and C 5 H 5 N), as illustrated in Fig.…”
Section: Gas Sensing Performancementioning
confidence: 99%
“…Metal oxides, including CeO 2 , TiO 2 , ZnO, Co 3 O 4 , and FeO x , have been extensively investigated as support for the SMSI effect. However, due to their poor conductivity, which limits their applicability as electrocatalyst supports in PEMFCs, more sophisticated SMSI support has been created, such as transition metal nitrides (TMNs). TMNs have gained significant attention due to their intermetallic nature, offering advantages such as high corrosion resistance, thermal stability, chemical stability, and excellent electrical conductivity. , Among the various TMNs, titanium nitride (TiN) has been extensively investigated; however, TiN continues to have slow corrosion issues in acidic situations. Conversely, CrN exhibits remarkable corrosion resistance, which has led to its use as a covering material for PEMFC bipolar plates. , In addition, CrN also has good conductivity and high-temperature stability, and even more recent studies raise the possibility that CrN has ORR-catalyzing action. More studies have suggested that nitride as a support has a beneficial regulatory influence on the ionomer distribution in the CL . Therefore, exploring the potential of TMNs, particularly CrN, as alternative catalyst supports for the ORR in PEMFCs holds promise for overcoming the limitations associated with conventional carbon-based catalyst supports.…”
Section: Introductionmentioning
confidence: 99%